DISKURSUS PEREMPUAN SEBAGAI KEPALA RUMAH TANGGA (TEORI FEMINIST JURISPRUDENCE) - Fatimawali, Fatimawali (Musawa: Journal for Gender Studies, 2024)
This study explores the "Discourse of Women as Heads of Households (Feminist Jurisprudence Theory)" with a focus on feminist jurisprudence theory's significant role in the field of legal studies, due to its ideas influencing many debates on sexual and domestic violence, workplace inequality, and gender-based discrimination. Through various approaches, feminists have identified gender components and the gender implications of legal norms and their supposedly neutral implementation, which have historically adversely impacted women in the contexts of employment, divorce, reproductive rights, rape, domestic violence, and sexual harassment. This research is a library research study, employing a qualitative research methodology, where primary data was collected by sourcing relevant books, supplemented by secondary data from articles, papers, news websites, etc. The study identifies gender-biased legal norms that affect women's roles as heads of households, particularly in terms of access to economic resources, family decision-making, and legal protection. Through a critical approach, this study also highlights the challenges faced by female heads of households in maintaining justice within the family, and the urgent need for legal reform to achieve better gender equality. Considering the perspectives from feminist jurisprudence theory, this research emphasizes the importance of changing phallocentric legal paradigms to accommodate the significant contributions of women in managing households and building a gender-inclusive society.